Digital twins: Recent advances and future directions in engineering fields - Kamran Iranshahi; Joshua Brun; Tim Arnold; Thomas Sergi; Ulf Christian Müller (Intelligent Systems with Applications)
Digital Twins have emerged as a powerful in silico method for the design, operation, and maintenance of real-world assets across various domains. This review paper investigates different aspects of Digital Twins, especially their application throughout the product lifecycle and across diverse engineering domains. It provides a comprehensive overview of different services that Digital Twins can deliver at each stage of the product lifecycle in collaboration with other digital technologies (e.g., Internet of Things, etc.) using a data chain (digital thread). The review begins with an introduction to Digital Twins, highlighting their fundamental principles and significance in engineering. It then explores various domains to provide cross-domain insights into the use of Digital Twins. These domains include manufacturing, healthcare and medicine, agriculture and food supply chain, aerospace, construction and building management, automotive and transportation. Each domain-specific section explores recent advancements, showcasing innovative approaches and how Digital Twins improve decision-making, while also addressing their current challenges. Furthermore, each section peers into the future, presenting a forward-looking perspective on the challenges and evolving landscape of Digital Twins in that specific engineering sector. Finally, it provides a panoramic view of the current status of Digital Twins in engineering fields, based on evaluations by a panel of experts. The expert panel assessed the Technology Readiness Level (TRL) of Digital Twins at 4.8 on a scale from 1 to 9. They identified the integration of Digital Twins with the digital thread as the most significant current challenge.